Re-Industrialization of Europe: Industry4.0 and the Future of Work - Kotynkova, Magdalena (European Scientific Journal, ESJ, 2017)
The term â€œIndustry 4.0â€ was first introduced in Germany in 2011. It refers to digitising industrial production. The concept outlines the vision of a smart factory, which is characterised by the complete networking of all production processes: real time control via ITC and the increased use of robots, which control themselves, are developments that should contribute to greater productivity and efficiency. The concept of Industry 4.0 is a base of re-industrialization of Europe. Industry 4.0 is shaping the digital discourse in the Czech Republic as well. The first step was the release of the National Initiative: Industry 4.0 by the Czech Ministry of Trade and Industry in 2015. We are now at the beginning of a fundamental debate that is still presenting more questions than offering answers. The aim of this paper is to discuss the issue: re-industrialization and its consequences for the world of work. If widespread predictions are correct, the digitisation of production can mean the extinction for millions of jobs. Innovations may seem grandiose, but they can also be destructive, rendering entire professions obsolete.